2020
DOI: 10.1111/geb.13064
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of biotic and abiotic determinants of temporal occupancy for avian species in North America

Abstract: Aim We examined the relative importance of competitor abundance and environmental variables in determining the species distributions of 175 bird species across North America. Unlike previous studies, which tend to model distributions in terms of presence and absence, we take advantage of a geographically extensive dataset of community time series to model the temporal occupancy of species at sites throughout their expected range. Location North America. Time period 2001–2015. Major taxa studied One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…However, despite such a potential bias, past work has shown that there is typically a positive relationship between either temporal occupancy or species richness and remotely sensed proxies for productivity, meaning the observed patterns were opposite what would be predicted purely from a detectability effect (7,17,23). As such, these patterns of occupancy and richness were observed despite, and not because of, geographic variation in detectability.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, despite such a potential bias, past work has shown that there is typically a positive relationship between either temporal occupancy or species richness and remotely sensed proxies for productivity, meaning the observed patterns were opposite what would be predicted purely from a detectability effect (7,17,23). As such, these patterns of occupancy and richness were observed despite, and not because of, geographic variation in detectability.…”
Section: Discussionmentioning
confidence: 88%
“…reproductive rate, dispersal distance), the inferences that can be made from this simulation model are more broadly generalizable. We chose to focus on birds because they are highly mobile, can disperse widely, and have been studied empirically in this core-transient context (3,7,23). These first two attributes make temporal occupancy particularly useful for identifying core and transient birds in communities, but also potentially more prone to errors due to sourcesink dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used temporal occupancy to infer the persistence of populations over time and the degree to which a species can be considered a core member of a community in a particular location [ 3 , 7 9 , 23 ]. Our simulations showed that in many realistic scenarios, this is a valid approach, but also confirmed that temporal occupancy is subject to misclassification errors where core species are inferred to be transient and transient species are inferred to be core.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic patterns in the relative prevalence of core and transient species can influence our understanding of ecological communities when failing to recognize this distinction [ 7 , 23 ], especially if the probability of misclassification varies geographically. One likely source for this is detection probability, which is thought to vary along environmental gradients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation